MIGRATION, ETHNICITY AND LOCAL POLITICS: THE CASE OF JAKARTA, INDONESIA - Aulia Hadi; Riwanto Tirtosudarmo (Populasi, 2016)
As the capital city of a country with the world’s fourth largest population, Jakarta, like many other big cities in the developing economies, for example, Mexico City or New Delhi, hosts migrants from all regions of the country. Without a doubt, Jakarta has increasingly become the major core of the agglomeration processes transforming it and its satellite cities into a Mega Urban Region (MUR). This paper traces historically the interactions between migration, ethnicities and local politics in Jakarta from the 1960s to the 2000s focusing on the latest development, in which the phenomenon ‘Ahok’, the nickname of Basuki Tjahaja Purnama, a Chinese-Christian from the small district of Belitung, has become an increasingly popular Governor of Jakarta. The paper argues that through the recent developments in Jakarta the politics have apparently been transformed into more civic, rather than ethnic politics. The nature of Jakarta as a proliferating migrant city transcends narrow cultural identities as well as conventional party politics into a more active citizenry through the widespread use of social media.